2007
DOI: 10.1523/jneurosci.2051-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Response Element-Binding Protein Deficiency Allows for Increased Neurogenesis and a Rapid Onset of Antidepressant Response

Abstract: cAMP response element-binding protein (CREB) has been implicated in the molecular and cellular mechanisms of chronic antidepressant (AD) treatment, although its role in the behavioral response is unclear. CREB-deficient (CREB ␣⌬ mutant) mice demonstrate an antidepressant phenotype in the tail suspension test (TST) and forced-swim test. Here, we show that, at baseline, CREB ␣⌬ mutant mice exhibited increased hippocampal cell proliferation and neurogenesis compared with wild-type (WT) controls, effects similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 59 publications
5
82
2
Order By: Relevance
“…Finally, our results showing that desipramine did not alter FST performance in or neurogenesis in control mice are somewhat surprising. Another study demonstrated that chronic desipramine treatment increases neurogenesis and decreases depression-like behavior in control mice; however, that study used utilized twice-daily administration of 12.5 mg/kg desipramine (Gur et al, 2007), indicating that a higher dose may have produced changes in our control animals. Additionally, although acute desipramine treatment has been shown to reduce immobility in the FST (Lucki et al, 2001), we did not administer desipramine on the day of the test.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, our results showing that desipramine did not alter FST performance in or neurogenesis in control mice are somewhat surprising. Another study demonstrated that chronic desipramine treatment increases neurogenesis and decreases depression-like behavior in control mice; however, that study used utilized twice-daily administration of 12.5 mg/kg desipramine (Gur et al, 2007), indicating that a higher dose may have produced changes in our control animals. Additionally, although acute desipramine treatment has been shown to reduce immobility in the FST (Lucki et al, 2001), we did not administer desipramine on the day of the test.…”
Section: Discussionmentioning
confidence: 96%
“…The cage was also sprayed with a cleaner (Pine Sol), and the experiment was performed in a novel testing room with no acclimation period. A failure to consume any milk was recorded as 15 min latency (Gur et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…(Gur et al, 2007) for 21 d to VGF ϩ/Ϫ and WT mice that had been trained to drink the sweetened condensed milk. Our results confirm that DMI injections administered intraperitoneally reduce the latency to drink in the novel environment relative to saline controls (F (2,13) ϭ 3.765, Fisher's p ϭ 0.0169) but had no effect on latency in the home cage on either day of testing (F (2,13) ϭ 0.875, Fisher's p ϭ 0.2566; F (2,13) ϭ 0.415, Fisher's p ϭ 0.8236).…”
Section: Vgf Mrna Is Reduced In the Hippocampus And Prefrontal Cortexmentioning
confidence: 99%
“…Closely related to this is the regulation of cAMP response element binding protein (CREB) levels in depression and by antidepressant treatment. A comprehensive review by Blendy indicates that there is evidence for both increased and decreased levels of CREB and pCREB following chronic treatment with certain antidepressants [2], and a later study discovered that CREB-deficient mice display a 'depression-resistant' phenotype [3].…”
mentioning
confidence: 99%
“…Thus, it appears that antidepressants may exert their observed effects on cAMP signaling by liberating G sα from TX-100-resistant membrane domains, where it accumulates during the course of depression. Furthermore, the ratio of TX-100-soluble to TX-100-resistant G sα may prove to be a useful biomarker for human depression and a rapid (3)(4) No writing assistance was utilized in the production of this manuscript.…”
mentioning
confidence: 99%